Jesaja 45:9-13: 'n Disputasie van Jahwe teen Israel of van Jahwe teen die heidennasies? - SL Stassen (Acta Theologica)
The most important issue to solve in Isaiah 45:9-13 is the question whether it is a disputation between Yahweh and Israel, the more orthodox viewpoint, or whether it should be interpreted as a disputation between Yahweh and the heathen nations, a viewpoint advocated by Leene and Beuken. the latter option assumes that the heathen nations are disputing Yahweh's love and preference for Israel as his elected people. If Isaiah 44:24-45:13 is taken as the context, however, it becomes clear that the more orthodox viewpoint is probably the more correct one. Therefore it can be assumed that Isaiah 45:9-13 and its context is the result of Israel disputing Yahweh's election of Cyrus, a heathen king, to deliver them from exile.